Diets supplemented with glutamate or glutamine improve protein retention and modulate gene expression of key enzymes of hepatic metabolism in gilthead seabream (Sparus aurata) juveniles - Caballero-Solares, Albert; Viegas, Ivan; Salgado, María C.; Siles, Ana M.; Sáez, Alberto; Metón, Isidoro; Baanante, Isabel V.; Fernández, Felipe (Aquaculture, 2015)
The present study evaluates the effect of dietary glutamate and glutamine supplementation on growth performance, body composition and expression of key enzymes involved in the hepatic metabolism of juvenile gilthead seabream (Sparus aurata). Fish were fed for 52days with four diets, which were identical in composition except for a 4% supplementation with glutamate (GLU diet), glutamine (GLN diet), carbohydrate (CHO diet) or bovine serum albumin (BSA diet). Glutamate and glutamine supplementation improved feed conversion ratio and protein retention compared to carbohydrate supplementation, and, in the case of glutamate, protein retention was improved over that of fish fed the protein supplemented diet. Feeding CHO and GLU diets resulted in up-regulation of glucokinase and lipogenic enzymes compared to fish fed GLN and BSA diets. Consistently, fish fed CHO or GLU diets showed higher triglyceride levels in serum and liver, and feeding the GLU diet resulted in higher body fat content than in fish fed GLN or BSA diets. The liver of fish fed GLN or BSA diets showed increased glutamate dehydrogenase activity in the direction of the glutamate oxidation. In contrast to fish fed the BSA diet, increased glutamate oxidation did not reduce free glutamine and glutamate levels in the liver of fish fed the GLN diet, suggesting that glutamine intake exceeded liver's energy requirements. In conclusion, glutamate supplementation improved hepatic glucose metabolism, whereas supplemented glutamine seems to be preferentially oxidized over amino acids derived from dietary protein, thus promoting higher protein retention in both cases. Our findings indicate that glutamate and glutamine could partly replace dietary protein and that glutamate supplementation could also facilitate protein replacement by carbohydrates in fish feeds. •Glutamate and glutamine supplementation improved FCR and protein retention compared to carbohydrate supplementation.•Glutamate supplementation improved protein retention compared to protein supplementation.•Glutamate supplementation enhanced liver glucose metabolism through stimulation of glycolysis, glycogenesis and lipogenesis.•Glutamine supplementation promoted glutamate oxidation by up-regulating glutamate dehydrogenase activity.